The right ventricle in congenital heart disease. (16th March 2006) - Davlouros, P A; Niwa, K; Webb, G; Gatzoulis, M A
Abstract : In patients with congenital heart disease the right ventricle (RV) may support the pulmonary (subpulmonary RV) or the systemic circulation (systemic RV). During the last 50 years evidence is accumulating that RV dysfunction develops in many of these patients and leads to considerable morbidity and mortality. Therefore RV function in certain groups of congenital heart disease patients needs close surveillance and timely and appropriate intervention to optimise outcomes. Despite major progress being made, assessing the RV either in the subpulmonary or the systemic circulation remains challenging, often requiring a multi-imaging approach and expertise (echocardiography, magnetic resonance imaging, nuclear and occasionally invasive assessment with angiography). This review discusses the implications of volume and pressure loading of the RV in the context of congenital heart disease and describes the most relevant imaging modalities for monitoring RV function.